Students attitude of physical education and healthy lifestyle and their self-assessment of physical fitness - Гринько Віталій Миколайович (Vitaliy Grinko) (Slobozhanskyi Herald of Science and Sport, 2015)
Purpose: to identify students’ attitudes toward physical education and healthy lifestyle, their own assessment of the level of physical fitness and physical qualities of priority. Material and Methods: conducted a questionnaire survey of students of Kharkiv National Economic University and Peter Vasilenko Kharkiv National Technical University of Agriculture. The study involved 166 first-year students (77 boys and 89 girls). Results: it was found that a positive attitude towards a healthy lifestyle and stick to it – 69,35% of the respondents; to physical education and are aware of the usefulness of employment – 84,8%; satisfied with their level of physical development – 40,65%. Conclusions: these results confirm the data that is currently experiencing a significant decline in the level of interest and motivation of students to a healthy lifestyle and physical education